(3GdCdaGXs - (3CHh fUQ Sgd Hf GdeQRHGf GdGTd GdfgGhfOj,J (B420 (3g` s ((3HYdHc s)
(3ChdgG (B:s
(3Ef Chdi , Ef CMb , Ef CLOQ , Ef CMQi , hEf CMLi , hEf CNdb gPG cJGH LeYfGg VQhHkG , CdafGg afhfkG hVYfGg CLfGSkG , haUdfGg aUhdkG s
(3BNQgG (B:s
(3HGH (B: (3NGaJ faSg , hEQJGY bdHg hhdg dHg , hWGQ Ybdg HGH (B: (3CjGO RGFOI , hbSe cGedI , hehGgH JGeI , hLhGFR ehajI , hfYe LeYI hYWGjG hGaQI , hefM JGeI Je GdcJGH HMeO Gddg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B143s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
Keywords: (3GddZIs